2018
DOI: 10.3390/e20100742
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Information Along Lifespan of the Resting Brain Dynamics Reveals a Major Redundant Role of the Default Mode Network

Abstract: Interaction Information (II) generalizes the univariate Shannon entropy to triplets of variables, allowing the detection of redundant (R) or synergetic (S) interactions in dynamical networks. Here, we calculated II from functional magnetic resonance imaging data and asked whether R or S vary across brain regions and along lifespan. Preserved along lifespan, we found high overlapping between the pattern of high R and the default mode network, whereas high values of S were overlapping with different cognitive do… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 56 publications
0
14
0
Order By: Relevance
“…Here we are describing in the connectome an organization that cannot be explained only in terms of pairwise node-to-node relationships. Interactions between more than a pair of nodes (high-order interdependencies) are described using information theory tools [42,43], giving rise to phenomena like redundancy and synergy that appear in the brain activity. These cannot be understood nor measured if only pairwise relationships are quantified.…”
Section: Discussionmentioning
confidence: 99%
“…Here we are describing in the connectome an organization that cannot be explained only in terms of pairwise node-to-node relationships. Interactions between more than a pair of nodes (high-order interdependencies) are described using information theory tools [42,43], giving rise to phenomena like redundancy and synergy that appear in the brain activity. These cannot be understood nor measured if only pairwise relationships are quantified.…”
Section: Discussionmentioning
confidence: 99%
“…Functional data were preprocessed using FSL (FMRIB Software Library, version 5.0) and AFNI, following a procedure similar to previous work (Diez et al, 2017; Rasero et al, 2017, 2019; Stramaglia et al, 2017; Bonifazi et al, 2018; Camino-Pontes et al, 2018). First, slice-time correction was applied to the fMRI.…”
Section: Methodsmentioning
confidence: 99%
“…A first study on high-order interactions and aging was reported in Ref. [20], which showed significant changes in synergies and redundancies in triple interactions along the lifespan, and a redundant role of the default mode network. The effect of aging on interactions beyond triple relationships is, to the best of our knowledge, still an unexplored territory.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we build upon Ref. [20] and study the effects of aging on the high-order interactions in the human brain, with a special focus on interdependencies between four or more brain regions. To this end, we employ the recently proposed O-Information [21], which can be considered to be revision of the measure of neural complexity proposed by Tononi, Sporns and Edelman [22] under the light of Partial Information Decomposition [23].…”
Section: Introductionmentioning
confidence: 99%